The Geometric Documentation of the Asinou Church in Cyprus - Sofocleous, E.; Georgopoulos, Andreas; Ioannides, Marinos; Ioannidis, Charalabos (My University, 2006)
The Asinou Church, devoted to the Virgin Mary, is a wonderful 11th c. Byzantine Church built up in Troodos Mountain on the island of Cyprus. This Church has been recognised as a World Heritage Monument by UNESCO. A joint effort between the Laboratory of Photogrammetry of NTUA and HTI had as main goal the geometric documentation of this monument, using a combination of modern digital techniques for data acquisition and methodologies for data processing. Digital surveying and photogrammetric instrumentation, as well as a laser scanner were employed, in order to collect the necessary data for producing digital colour orthophotographs for the four exterior facades and six interior crossections of the church. The methodology is briefly described and assessed for its adaptability to the special requirements of this monument. The results of the data processing are presented and evaluated for their usefulness. Moreover a 3D visualisation of the church is attempted based on the accurate measurements performed. The paper concludes with an appraisal of the products in view of their inclusion in a Monument Information System, which could include all monuments of the particular area of Cyprus.
Keywords: Asinou Church; 3D visualisation